Natural history of Xenosaurus phalaroanthereon (Squamata, Xenosauridae), a Knob-scaled Lizard from Oaxaca, Mexico - Lemos-Espinal, Julio A.; Smith, Geoffrey R. (Phyllomedusa: Journal of Herpetology, 2005)
We made observations on the natural history of a population of the lizard Xenosaurus phalaroanthereon from Oaxaca, Mexico. Females were larger than males (SVL). Most lizards were found completely inside rock crevices. Mean body temperature was 20.3ºC. Body temperature was related primarily to substrate temperature. Body temperature was not influenced by any crevice characteristic. Based on abdominal palpation, the size at maturity for females appears to be 117-119 mm SVL. Sex ratio did not differ from 1:1. We compare the ecology of this population to that of other Xenosaurus.